A Critical Investigation of Cerebellar Associative Learning in Isolated Dystonia. Issue 6 (21st March 2022) - Sadnicka, Anna; Rocchi, Lorenzo; Latorre, Anna; Antelmi, Elena; Teo, James; Pareés, Isabel; Hoffland, Britt S.; Brock, Kristian; Kornysheva, Katja; Edwards, Mark J.; Bhatia, Kailash P.; Rothwell, John C.
Abstract: Background: Impaired eyeblink conditioning is often cited as evidence for cerebellar dysfunction in isolated dystonia yet the results from individual studies are conflicting and underpowered. Objective: To systematically examine the influence of dystonia, dystonia subtype, and clinical features over eyeblink conditioning within a statistical model which controlled for the covariates age and sex. Methods: Original neurophysiological data from all published studies (until 2019) were shared and compared to an age‐ and sex‐matched control group. Two raters blinded to participant identity rescored all recordings (6732 trials). After higher inter‐rater agreement was confirmed, mean conditioning per block across raters was entered into a mixed repetitive measures model. Results: Isolated dystonia ( P  = 0.517) and the subtypes of isolated dystonia (cervical dystonia, DYT‐TOR1A, DYT‐THAP1, and focal hand dystonia) had similar levels of eyeblink conditioning relative to controls. The presence of tremor did not significantly influence levels of eyeblink conditioning. A large range of eyeblink conditioning behavior was seen in both health and dystonia and sample size estimates are provided for future studies. Conclusions: The similarity of eyeblink conditioning behavior in dystonia and controls is against a global cerebellar learning deficit in isolated dystonia. Precise mechanisms for how the cerebellum interplays mechanistically with other key neuroanatomical nodes within the dystonic network remains an open research question. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society.